2008
DOI: 10.1093/glycob/cwn006
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Hyal3 encodes a 45- to 56-kDa glycoprotein whose overexpression increases hyaluronidase 1 activity in cultured cells

Abstract: Hyaluronidases are enzymes that mediate the breakdown of hyaluronan (HA), a large polysaccharide abundant in the extracellular matrix of vertebrate tissues. Six genes have been predicted to encode hyaluronidases in humans, but the protein products of only SPAM1, HYAL1, and HYAL2 have been characterized. We have now expressed the mouse Hyal3 gene product, hyaluronidase 3 (Hyal3), in Baby Hamster Kidney (BHK) cells and demonstrated the presence of multiple forms of Hyal3 ranging from approximately 45 to 56 kDa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 42 publications
5
47
0
Order By: Relevance
“…4A). The two Hyal-1 protein bands observed (50 and 55 kDa) were presumably from a different glycosylation level of this enzyme (17). The in situ hybridization results supported those of the protein expression; the level of Hyal-1 mRNA (localized predominantly in small antral follicles) was higher in the younger mice (Fig.…”
Section: Hyaluronidase Expression Correlates With Atretic Follicles Asupporting
confidence: 72%
See 3 more Smart Citations
“…4A). The two Hyal-1 protein bands observed (50 and 55 kDa) were presumably from a different glycosylation level of this enzyme (17). The in situ hybridization results supported those of the protein expression; the level of Hyal-1 mRNA (localized predominantly in small antral follicles) was higher in the younger mice (Fig.…”
Section: Hyaluronidase Expression Correlates With Atretic Follicles Asupporting
confidence: 72%
“…6), which contained no enzymatic activity (Fig. 5A) (16,17), strongly suggested that the hyaluronan processing (or the hyaluronidase enzymatic activity) was not relevant to cell apoptosis. Nonetheless, the close association between the hyaluronidase expression and cell apoptosis remained.…”
Section: Induction Of Granulosa Cell Apoptosis By Hyaluronidase Is Nomentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, our data indicating that that NADPH oxidase regulates Hyal3 expression in VSMC treated with thrombin is significant because increased HA during pathological conditions is the sum of its synthesis and catabolism. This is also an interesting observation because Hyal3 Ϫ/Ϫ mice do not exhibit any HA accumulation (57) and cellular overexpression of Hyal3 does not impart intrinsic hyaluronidase activity (58). In contrast, up-regulation of Hyal3 was reported in chondrocytes treated with cytokines (59).…”
mentioning
confidence: 88%